ANALISIS PENGARUH FINANCIAL BEHAVIOR DAN INCOME TERHADAP KEPUTUSAN BERINVESTASI MASYARAKAT KOTA PANGKALPINANG (STUDI KOMPARASI SEBELUM DAN SESUDAH PANDEMI COVID-19) - Wenni Anggita (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2023)
Investment is a sacrifice of funds and financial preparation in order to gain future profits. Investment decisions are important in income management. The tendecy to think short term and implusive shopping practices often make individuals with sufficient income still experience financial problem due to irresponsible financial behavior. Many factors are assumed to influce differences in investment decisions as well as the covid-19 pandemic that affects people’s financial behavior and income. This study aims to see whether financial behavior and income affect investment volatility and the difference before and after the pandemic in the people of Pangkalpinang City. This study use theory of planned behavior (TPB) that behavioral control can directly affect investment decisions. This research is a quantitative research. Comparative method. Using primary data with purposive sampling methode based on criteria, 30-50 years old generation and investors/non-investors who know about investment. Multiple liniear regression analysis and comparative effect used to analyze the research. The result showed that financial behavior affects people’s investment decisions before the pandemic. Meanwhile, financial behavior does not affect investment decisions after the pandemic. Income has no effect on people’s investment decisions before and after the pandemic. There are differences in the influence of financial behavior on investment decisions before and after the pandemic. Meanwhile, there is no difference in income distribution on investment decisions before and after the pandemic.